Discovering Accessible Financial Systems Resources for Emergent Users - Teran, Luciano Arruda (2025)
The widespread use of mobile phones in Brazil has significantly altered information access and communication, impacting the financial sector as institutions increasingly use mobile apps. However, ensuring accessibility for all users remains challenging, particularly for riverside people who lack exposure to formal education, urban environments, and digital technologies. This study examined the accessibility and communicability barriers this population faces in mobile banking applications, especially in instant payment features. After reviewing best practices and applying the Semiotic Inspection Method (SIM), the study developed and tested an instant payment prototype with riverside people in the Amazon region. Interviews and the Communicability Evaluation Method (CEM) were used to measure communication effectiveness and inform design improvements for Pix interfaces. Afterward, a workshop with computing students was conducted, and they showed interest in inclusive systems but needed more practical knowledge. The workshop also highlighted the necessity of providing audio resources, more security, and illustrations and text that are easy to understand in financial conversation systems for emergent users. This research supports digital inclusion by exploring resources to improve accessibility in interactive systems for emergent users.